Problem Based Learning Model Effectiveness in Improving Learning Achievement of Class X MIA Students on Newton's Law II Material in Offline and Online Learning - Nuranna Nuranna (Journal La Edusci, 2021)
This study aims at investigating the effectiveness of Problem Based Learning in enhancing students’ achievement. The design of this research is that of a quasi-experimental kind. The information was collected from two different courses that were both at the same grade level and covering the same subject. The data that was compared came from a variety of historical periods. The control group was recruited before to the outbreak, while the second group was recruited via an online learning session after the pandemic had begun. A pre-test is administered to see if any of the students have previous knowledge of the subject matter that will be taught. Pre-testing may also be thought of as an activity that is used to assess the level of knowledge of the students prior to the delivery of the learning activities itself. The results of the study suggest a slight difference when students are taught using PBL with online and offline learning. There is a conspicuous challenge in online learning due to teacher’s and students’ customization to online learning.